3nuts: A Locality-Aware Peer-to-Peer Network Combining Random Networks, Search Trees, and DHTs - Schindelhauer, Christian; Mahlmann, Peter; Janson, Thomas
Categorizing peer-to-peer networks from an algorithmic point of view the two extremes of the spectrum are unstructured networks and networks based on plain distributed hash tables (DHT). Unstructured networks stand out with their simplicity, robustness, and support for complex queries. Though, they lack efficient query algorithms providing guarantees. On the other hand, DHT based networks feature efficient lookup algorithms with typically logarithmic hop distance and provide simple and efficient load balancing. Yet, they are limited to exact match queries and in many cases hard to maintain under churn.